Synthesis of simplified analogues of eleutherobin via a Claisen rearrangement/RCM strategy - Mak, S; Chiang, G; Davidson, J; Davies, J; Ayscough, A; Pain, G; Burton, J; Holmes, AB (2009)
The enantioselective synthesis of a number of simplified analogues of the cytotoxic natural product eleutherobin is reported. © 2009 Elsevier Ltd. All rights reserved.